Influence of tire pass on soil stress transfer and particle cohesion via DEM simulation - Mingyue Bai; Xianliang Wang; Haiyang Zhuang; Wenqi Zhao; Weifan Zhou (Revista Brasileira de Ciência do Solo)
ABSTRACT Stress transfers inside the soil during the traveling process of agricultural machinery, and the bonding of soil particles during this process is the main cause of soil compaction. In this study, the discrete element method was used to simulate the different responses of stress transfer and particle bonding in the soil under different times of tire passes in the tire-soil interaction process of agricultural machinery operation. It was found that from 1 to 8 passes, the increase in the times of tire passing caused the soil stress to transfer from the depth of 0.20 to 0.70 m, with the maximum stress reaching 27.36 kPa. The number of force chains between soil particles increased gradually with the increase in the times of tire passing, and the number of force chains risen from 12,058 to 14,515. This indicated that there was an inextricable link between tire passes and the formation of cumulative compaction in soil. The results of this study verified the validity of the DEM model based on PFC3D, providing a theoretical basis for the subsequent research on soil mechanical compaction technology for mitigating soil compaction caused by agricultural machinery and equipment.